Comparative analysis of furosemide and torsemide efficacy in 24 hours of acute heart failure admission - Małek-Elikowska, Małgorzata; Szyszka, Andrzej; Fedorowicz, Julita; Dankowski, Rafał; Szymańska, Cyntia; Baszko, Artur (Frontiers in Pharmacology, 2025)
BackgroundIntravenous (IV) furosemide and torsemide represent a cornerstone of guideline-directed medical therapy for acute heart failure (AHF). However, the evidence regarding the superiority of each agent remains controversial.MethodsThe prospective, open-label, comparative study included 51 adult patients hospitalized due to AHF. Torsemide was administered to 25 patients (49%), and furosemide to 26 patients (51%). The primary endpoint was the change in urinary spot sodium level at 24 h, used to assess diuretic efficacy. Secondary outcomes included lung ultrasound (LUS) B-lines, clinical status evaluation based on the Borg scale, Killip-Kimball classification, and daily urine output.ResultsAfter 24 h of treatment, urinary sodium levels increased by an estimated marginal mean (EMM) of 21.84 mmol/L in the furosemide group and 0.97 mmol/L in the torsemide group (p = 0.173). The number of B-lines over 24 h decreased, with an EMM of 28.31 in the furosemide group, and 30.12 in the torsemide group (p = 0.779). The severity of dyspnea, measured by the Borg scale, decreased over 24 h with an EMM of 3.58 points in the furosemide group, and 3.62 points in the torsemide group (p = 0.891). Pulmonary congestion, measured by the Killip-Kimball classification, minimized with an EMM of 0.42 points in the furosemide group, and 0.47 points in the torsemide group (p = 0.770). Daily urine output after 24 h of treatment reached an EMM of 3,559.67 mL in the furosemide group, and 2,734.89 mL in the torsemide group (p = 0.068).ConclusionBoth furosemide and torsemide demonstrated comparable efficacy in the initial treatment of AHF, as assessed by laboratory, ultrasound, and clinical parameters.